Introducing radical democratic citizenship: from practice to theory. Issue 1 (2nd January 2022) - Zaunseder, Andreas; Woodman, Sophia; Emejulu, Akwugo
ABSTRACT: For our special issue, 'Radical Democratic Citizenship: From Practice to Theory', we examine different forms of radical theorising and politics at the grassroots. Radical democratic citizenship entails forms of struggle against gross social, economic and political miseries and injustices. This special issue explores the implications of a renewed wave of revolutionary grassroots action. 'Radical' indicates firstly the potential for sustained fundamental change of the economic and political landscape that, secondly, is pursued from the grassroots, and, thirdly, through an egalitarian, democratic process that are transformative in rethinking and reshaping the parameters of what democracy can and should be. We raise the question of how localised alternatives -– which have been the most fertile terrain for such generation of different worlds – might be able to address wider questions of global inequality on our finite planet.